CAMPUR KODE DAN ALIH KODE PADA ANAK USIA 7 TAHUN DI DESA KOTO BURUK KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Okma Permata; Ance Jusmaya; Maharani Putri (Ensiklopedia Research and Community Service Review, 2026)
Abstract: The system of communication used by humans in general is language. The language we know is not only the national language, but there are also regional languages that we must learn to maintain its sustainability and also English as a foreign language that also needs to be learned. The phenomenon of language pronunciation in children is still mixed and shifting one language to another. This study aims to determine the code mixing and code switching used by 7-year-old children in Koto Buruk Village, Lubuk Alung District, Padang Pariaman Regency. This study uses a qualitative descriptive method. The data processing and data collection techniques are carried out through observation, interviews, recordings, and notes. The subjects in this study were 7-year-old children in Koto Buruk Village, Lubuk Alung District, Padang Pariaman Regency. The results of this study indicate that the use of language in 7-year-old children still has a mixture and shifting language. The existence of code mixing and code switching used by 7-year-old children is a language that is mastered by listening to other people's conversations, so that the arrangement of vocabulary is still messy. So, when using language in front of children, it's better to place the language so that the vocabulary the child hears is structured and not mixed up.Keywords: Code Mixing, Code Switching